PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Widdy Kristianto; Prima Apriwenni (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
The purpose of financial reporting is to provide information regarding the financial position, performance, and changes in the financial position of an entity that is beneficial to a large number of users in economic decision-making. Timeliness is an important component that can improve the quality of financial information. Financial information is timely if the information is available to decision-makers before losing capacity to influence decisions.. The purpose of this study is to test whether profitability (ROA), solvency (DER), firm size, and audit opinion affect the timeliness of financial reporting in consumer goods companies listed on Indonesia Stock Exchange in 2013-2016.The object of this research is 24 Consumer Goods companies listed on Indonesia Stock Exchange in 2013-2016. Sampling technique used is Non-Probability Sampling technique, using purposive sampling method. Analytical methods used are descriptive straticistic test, coefficient equality test, classical assumption test, and multiple linear regression analysis.The conclusion of this research indicates that profitability (ROA) has a positive effect on timeliness. solvency (DER) has a negative effect on timeliness. While firm size and audit opinion have no effect on timeliness.